Understanding parasite transmission through imaging approaches - Singer, Mirko; Frischknecht, Friedrich (Imaging and spectroscopic analysis of living cells, 2012)
Unicellular parasites are of high medical relevance as they cause such devastating diseases as malaria or sleeping sickness. Besides the search for improved treatments, research on these parasites is valuable as they constitute interesting model cells to study basic processes of life. They can also serve as valuable reality checks for our presumed understanding of biological processes that emerge from the study of human or yeast cells, as our common ancestor with many parasites is much older than the one with yeast. But working with parasites can be tricky and time-consuming, if not outright impossible. Here, we focus on examples from imaging studies investigating the transmission of the malaria parasite. Achieving an understanding of the processes important for malaria transmission necessitates different imaging approaches and new molecular and material technologies. The discussed techniques will include in vivo imaging of pathogens in living animals, screening methodologies, and new materials as surrogate 3D environments.